Wnt Signaling Cascades and the Roles of Syndecan Proteoglycans - Pataki, Csilla A; Couchman, John R; Brábek, Jan (The journal of histochemistry and cytochemistry, 2015)
Wnt signaling comprises a group of pathways emanating from the extracellular environment through cell-surface receptors into the intracellular milieu. Wnt signaling cascades can be divided into two main branches, the canonical/β-catenin pathway and the non-canonical pathways containing the Wnt/planar cell polarity and Wnt/calcium signaling. Syndecans are type I transmembrane proteoglycans with a long evolutionary history, being expressed in all Bilateria and in almost all cell types. Both Wnt pathways have been extensively studied over the past 30 years and shown to have roles during development and in a multitude of diseases. Although the first evidence for interactions between syndecans and Wnts dates back to 1997, the number of studies connecting these pathways is low, and many open questions remained unanswered. In this review, syndecan's involvement in Wnt signaling pathways as well as some of the pathologies resulting from dysregulation of the components of these pathways are summarized.
Keywords: heparan sulfate; nemoc; disease; Wnt Signaling Pathway; syndecan; signální dráha Wnt; Disease; non-canonical Wnt pathway; zvířata; Humans; canonical Wnt pathway; Syndecans; syndekany; lidé; Animals